The Growth of E-Government in the Government of Yogyakarta City - DANANG SRI WIBOWO; IRWAM ABDULLAH; MUHADJIR DARWIN (Jurnal Studi Pemerintahan, 2014)
The implementation of e-government is, actually,not a new issue in the government. However, thepolicy of e-government implementation in manygovernmental elements, especially in the localgovernment seems to be forced withoutconsidering the different readiness levels of thegovernment personnel and the people in each localgovernment. On the one side, many researchfindings show that the factors of governmentalhuman resources, the public, the infrastructure, andthe working practice are still being obstacles toachieve a successful e-government implementation.On the other hand, other research findings alsostrengthen that in its implementation, egovernmenthas some elements which should befulfilled. They are e-administration, e-services, ande-society. Three of them are unified elements whichsupport each other in order to realize egovernment.Many problems faced by some localgovernments in implementing e-government,including the government of Yogyakarta City, clarifythat there are fundamental problems in realizingthe e-government elements which consist of eadministration,e-services, and e-society. For certaingovernmental institutions, an explanation of therelationship between the implementation of egovernmentprogram and many available theories isa valuable contribution to solve inter-elementsrelationship for realizing good governance, on theone hand, and, on the other hand, it is alsobeneficial for them to learn best practice for thegovernment in order to achieve good localgovernance. The results of this study show that theimplementation of e-government which requiresthe availability of e-administration, e-services, ande-society has been realized by the government of Yogyakarta City.However, although those programs have been realized physically, onthe actual, the unpreparedness of the government personnel as wellas the public society and also the cultural factors are still being someproblems which impede the successful implementation of egovernment.In addition, the city government’s commitment to keepcontinuing the easy service development to the community is a keyto the implementation of e-government in the scope of citygovernment in Yogyakarta.